Household income distribution impact of public expenditure by component in Malaysia - Harun, Mukaramah; Abdul Jalil, Ahmad Zafarullah; Abu Bakar, Nor'Aznin (2012)
This paper analyzes the impact of public expenditure by its components on income distribution among household sectors in Malaysia. The study on public expenditure related to income distribution is important as public expenditure has been used intensively since independence to achieve income equality goals in Malaysia. However, income inequality across ethnic groups, urban and rural areas remains wide and persistent. Income for Chinese and Indian is more than one time higher the income for Malay while income for urban is approximately double the income for rural.Using a detailed SAM framework for Malaysia constituting 50 accounts and a fixed price multiplier model, this paper highlights the difference impacts of public expenditure by different components on income distribution.Our results show that while public expenditure in education has improved inter-ethnic income inequality, it has led to a widening of rural-urban disparity. Furthermore, expenditure in agriculture and rural development are shown to have a positive impact on both inter-ethnic income inequality and rural-urban disparity.